What’s Love Got to Do With It? Badiou’s Scene of Two Through the Lens of Lacan's Formulas of Sexuation - Van Laeken, Alexandra (Filozofski vestnik, 2024)
Badiou’s philosophy deals with the question of radical change, most prominently in relation to love and emancipatory politics. Yet, he notes that love and politics are not interwoven and must be dealt with separately. In recent literature, Lacan’s theory of sexuation and love has been extensively drawn upon and put into relation with politics (notably by Žižek and Zupančič). It is striking that Badiou, being both a highly political thinker and strongly influenced by Lacan, only discusses sexuation in relation to love, but disconnects the concept from politics. In this paper, I probe Badiou’s concept of love in light of Lacan’s formulas of sexuation. I first examine Badiou’s concepts of love and politics in relation to sexuation, then set this against Lacan’s formulas, to eventually illustrate the political relevance of love.